2015
DOI: 10.3389/fped.2015.00032
|View full text |Cite
|
Sign up to set email alerts
|

Three-Weekly Doses of Azithromycin for Indigenous Infants Hospitalized with Bronchiolitis: A Multicentre, Randomized, Placebo-Controlled Trial

Abstract: BackgroundBronchiolitis is a major health burden in infants globally, particularly among Indigenous populations. It is unknown if 3 weeks of azithromycin improve clinical outcomes beyond the hospitalization period. In an international, double-blind randomized controlled trial, we determined if 3 weeks of azithromycin improved clinical outcomes in Indigenous infants hospitalized with bronchiolitis.MethodsInfants aged ≤24 months were enrolled from three centers and randomized to receive three once-weekly doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 34 publications
(71 reference statements)
1
70
1
1
Order By: Relevance
“…However, we wish to highlight that 5 RCTs have already been published evaluating different doses and durations of macrolides for those hospitalized with bronchiolitis. [2][3][4][5][6] Nonetheless, just 1 small RCT comprising 30 infants 2 was cited as the ''only previous trial for the prevention of post-RSV wheezing.'' 1 This Turkish study reported clinically improved outcomes during hospitalization and contrasts with the other 4 trials (range, 71-219 subjects) in which no clinical benefits were detected in infants from The Netherlands, Brazil, Australia, and New Zealand.…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…However, we wish to highlight that 5 RCTs have already been published evaluating different doses and durations of macrolides for those hospitalized with bronchiolitis. [2][3][4][5][6] Nonetheless, just 1 small RCT comprising 30 infants 2 was cited as the ''only previous trial for the prevention of post-RSV wheezing.'' 1 This Turkish study reported clinically improved outcomes during hospitalization and contrasts with the other 4 trials (range, 71-219 subjects) in which no clinical benefits were detected in infants from The Netherlands, Brazil, Australia, and New Zealand.…”
Section: To the Editormentioning
confidence: 99%
“…1 This Turkish study reported clinically improved outcomes during hospitalization and contrasts with the other 4 trials (range, 71-219 subjects) in which no clinical benefits were detected in infants from The Netherlands, Brazil, Australia, and New Zealand. [3][4][5][6] However, only 3 of the 5 published RCTs reported clinical data beyond the hospitalization period. 2,5,6 The Turkish study suffered an attrition rate of 30%, leaving only 21 infants to be followed for the next 6 months, with 1 of the 12 infants allocated 3 weeks of daily clarithromycin and 4 of the 9 treated with placebo requiring a respiratory illness readmission, a result that did not reach statistical significance.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Randomised controlled trials of antibiotic treatments for paediatric bronchiolitis, most commonly caused by RSV, have found limited effect on clinical outcomes like length of hospitalisation stay, despite reductions in bacterial load in the URT (72)(73)(74). Thus, there are concerns that in many paediatric ARI cases, antibiotic prescriptions are unjustified and potentially contribute to the development of antibiotic resistance (70).…”
Section: Treatment and Preventionmentioning
confidence: 99%